2015
DOI: 10.1097/opx.0000000000000711
|View full text |Cite
|
Sign up to set email alerts
|

Accommodative Gain in Relation to Perceived Target Clarity

Abstract: Purpose The purpose of this study is to determine the relationship between target clarity and the magnitude of accommodative lag using the metric accommodative gain (AG). Methods Monocular accommodative responses were measured with Grand Seiko autorefraction using both proximal and minus lens techniques in 139 subjects 5–35 years old. Subjects viewed a 1.5mm letter at 13 discrete distances (range = 40 – 3.33cm) for the proximal technique and fixed at 33cm through minus lenses of increasing power for the lens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The magnitude of lag does not always correlate to levels of perceived blur (Figure 3). 17 Additionally, it has also been shown that there is a “dipper” effect in which the threshold for blur detection slightly improves when the reference blur (e.g. : the clear letter) is also out of focus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of lag does not always correlate to levels of perceived blur (Figure 3). 17 Additionally, it has also been shown that there is a “dipper” effect in which the threshold for blur detection slightly improves when the reference blur (e.g. : the clear letter) is also out of focus.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, increased accommodative lag may occur due to an increased depth-of-focus which is associated with an increase in accommodative effort. 7, 17…”
mentioning
confidence: 99%
“…2, Table 2), which supports the afferent pathway hypothesis for an increase in accommodative microfluctuations. Greater accommodative demands have been associated with larger accommodative lags in children and adults 4347. Higher accommodative demands, also have been associated with increases in the depth-of-focus 42.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we used the WAM-5500 autorefactor, which has been demonstrated to be an accurate tool for quantifying accommodation in both static and dynamic modes, and in different contexts and experimental conditions. 34,35,[43][44][45] The WAM-5500 can acquire continuous recordings of accommodation and pupil size in the dynamic mode (high-speed), with a sensitivity of 0.01 D and 0.1 mm, respectively, and a temporal resolution of approximately 5…”
Section: Dynamic Accommodative Response Assessmentsmentioning
confidence: 99%
“…Interestingly, we found a lower variability, although significant between both correction methods (see figure 2), at 40 cm distance. This length is considered as the habitual distance for near tasks in the vast majority of nonpresbyopic adults, 45,61 and it is also the normalized distance used in optometric examinations for near tests. 40 We support the contention that the visual functioning may be adapted to the habitually used distance in the real life.…”
Section: Variability Of Accommodative Responsementioning
confidence: 99%